NASIKH-MANSUKH DALAM AL QUR'AN - Hadi, Abdul (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2016)
The concept of nasikh and mansukh is a very vital discussion for a mufassir to avoid mistakes and mistakes in capturing the intent of the Koran. The problem of nasikh and mansukh, during this time is still a debate among the scholars mufassirin, ie between scholars who support and reject it. However, the establishment of an Islamic law does not mean that it has become a final decision, it could have changed as historical development and change. Differences of opinion among scholars mufassirin about the existence or absence of nasakh in al-Quran, it should be underlined in general ulama ittifaq about the occurrence of naskh in al-Quran.